A Reference Genome from the Symbiotic Hydrozoan, Hydra viridissima. Issue 11 (1st November 2020) - Hamada, Mayuko; Satoh, Noriyuki; Khalturin, Konstantin
Abstract: Various Hydra species have been employed as model organisms since the 18 th century. Introduction of transgenic and knock-down technologies made them ideal experimental systems for studying cellular and molecular mechanisms involved in regeneration, body-axis formation, senescence, symbiosis, and holobiosis. In order to provide an important reference for genetic studies, the Hydra magnipapillata genome (species name has been changed to H. vulgaris ) was sequenced a decade ago (Chapman et al., 2010 ) and the updated genome assembly, Hydra 2.0, was made available by the National Human Genome Research Institute in 2017. While H. vulgaris belongs to the non-symbiotic brown hydra lineage, the green hydra, Hydra viridissima, harbors algal symbionts and belongs to an early diverging clade that separated from the common ancestor of brown and green hydra lineages at least 100 million years ago (Schwentner and Bosch 2015 ; Khalturin et al., 2019 ). While interspecific interactions between H. viridissima and endosymbiotic unicellular green algae of the genus Chlorella have been a subject of interest for decades, genomic information about green hydras was nonexistent. Here we report a draft 280-Mbp genome assembly for Hydra viridissima strain A99, with a scaffold N50 of 1.1 Mbp. The H. viridissima genome contains an estimated 21, 476 protein-coding genes. Comparative analysis of Pfam domains and orthologous proteins highlights characteristic features of H. viridissima, such as diversification of innate immunity genes that are important for host-symbiont interactions. Thus, the H. viridissima assembly provides an important hydrozoan genome reference that will facilitate symbiosis research and better comparisons of metazoan genome architectures.